Synthesis, structural and spectral characterization, and in vitro nuclease activity of new thiosemicarbazone derivatives - Hussein, Mouayed Abdulaali; Guan, Teoh Siang (European Journal of Chemistry, 2016)
Two new compounds, (E)-2-(3-ethoxy-2-hydroxybenzylidene)hydrazinecarbothioamide (1) and (E)-N-ethyl-2-((2-hydroxynaphthalen-1-yl)methylene)hydrazinecarbothioamide (2) have been synthesized. The prepared compounds have been characterized by CHN analysis, FT-IR, UV-Vis, 1H and 13C NMR spectroscopic techniques as well as the fluorescence emission spectroscopy. The molecular structures of the compounds have also been determined by X-ray single crystal diffraction analysis. The crystal structures revealed that the compounds are remain as a thione form in the solid state and are different in their geometrical, conformational and symmetrical structures. The nuclease activity of compounds to cleave pBR 322 has been investigated using agarose gel electrophoresis assay. The compound 2 revealed a significant nuclease activity which was attributed to the lipophilic properties that provided by substituent moieties of the compound.